Dental Prosthesis Identification for Medical Students - Steven Curtis (Association of American Medical Colleges, 2013)
Abstract A significant percentage of emergency room visits are dental related. A proportion of these are due to dental prosthesis pathology. Some prosthesis problems lend themselves to easy solutions in the emergency room. Others require referral to a dentist. This guide will enable non-dentists to recognize dental prostheses and some of their pathology using radiographs of common dental prostheses in the respiratory and alimentary systems. Also included are common pathology caused by poorly maintained or failing prostheses. Some prostheses and instruments are sometimes aspirated or swallowed, which is why it is also important for medical students to know what prostheses need to be removed prior to airway procedures.